Le développement professionnel des enseignants expérimentés par la transmission explicite de pratiques ordinaires entre pairs - Stéphane Talérien; Sébastien Chaliès; Stefano Bertone (Recherches en Éducation)
This case study is part of an anthropocultural research program in which the main theoretical assumptions are borrowed from the philosophy of ordinary language (Wittgenstein, 2004). The research aims to study the effects on professional development of a training program that is part of a continuous training format called "adaptive". This system attempts to create the formal conditions for the effective transmission of ordinary practices between two experienced teachers (one acting as a "peer trainer" and the other as a "trained peer") and thus produce professional development. To this end, it proposes three adjustments to the traditional training format: (i) prior access by the peer trainer to a synoptic vision of the rules governing his practice to be transmitted (ii) ostensibly taught by the peer trainer to the trained peer and (iii) two implemented by the trained peer followed in each case by a mentoring activity in the form of peer trainer control. The results obtained show (a) effective learning of the rules by the trained peer following the access of the peer trainer to a clearer vision of the rules underlying his practice and following his support activity, as well as (b) the development of the professional activity of the trained peer through the monitoring and interpretation of the rules learned under new circumstances.